Undergraduate Students' Perception on The Use of Role-Play In Speaking Class - Natalia Anggrarini; Indah Trianasari (National Conference on Language, Education, and Technology Proceeding, 2022)
This study aims to analyze the undergraduate students’ perception of role-play in speaking class that focuses on self-concept and speaking ability. The researchers employed a case study of twenty-five undergraduate students who had attended speaking subject with role play as the activity in the learning process. The data were collected by distributing 25-item questionnaires and open-ended interviews to confirm the questionnaire data. The researchers analyzed the questionnaire data quantitatively with mean formulation followed by range score category for the interview data descriptively. The results reported that the student’s perception of the use of role-play and their self-concept gained a high score. The students perceived that role play is a suitable and effective technique in speaking class. It helps them to communicate effectively through the use of a script. It also builds self-confidence and motivation to improve their speaking ability. In speaking activities, role play is perceived to create satisfaction and a comfortable and interesting atmosphere. The students are challenged to perform better due to the massive space of practice with their friends with the real life and familiar situation brought to the activity. This study implies that speaking activities with role play to be conducted more frequently and cover more meaningful and contextual topics for the students. This study suggests a comprehensible investigation of the factors underlying the students’ confidence in speaking with role play as the activity.